Healing Richard Nixon : a doctor's memoir - Lungren, John C. M. D. (The University Press of Kentucky, 2015)
Richard M. Nixon remains an enigma even thirty years after his resignation. Of the many portraits of this complex man, none have been more intimate or revealing than this memoir from his personal physician, friend, and confidante of more than forty years, John C. Lungren, M.D. Dr. Lungren, with his son and co-author John C. Lungren Jr., portrays Nixon as a paradoxical man -- intense, compassionate, guarded, intelligent, resilient, deeply religious, enormously successful but ultimately tragic. Lungren describes his battle to restore the president's health after his resignation and reveals previo.